Customer Decisions to Use Online Food Delivery Services During The COVID-19 Pandemic - Falah Fadjariansyah Kusuma Kautsar; Manahan Siallagan; Yonathan Palumian (Journal of Business and Management Review, 2023)
The coronavirus disease pandemic restricted dine-in service, and restaurants should adapt and rely heavily on no-contact operations and online food delivery services to sustain. Even though online food delivery technology is widely used in the food and beverages business, there is only a few research investigating the customers' behavior intention on online food delivery technology in the coronavirus disease pandemic. This study aims to investigate the influencing factor of behavior intention on online food delivery platforms, by applying the technology acceptance model. An online questionnaire was applied to conduct the survey. The Partial Least Squares-Structural Equation Modeling approach was used to examine 417 respondents empirically. The results showed the significance of perceived usefulness, trust, social influence, and value co-creation in customer intention on online food delivery technology. The findings contribute to the body of knowledge about technology acceptance in an emergency event, specifically during a coronavirus disease pandemic. The practical implication of the study is managers of online food delivery services firms must identify their customers' wants and needs.